2018
DOI: 10.1002/jso.25005
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction using a constrained‐type hip tumor prosthesis after resection of malignant periacetabular tumors: A study by the Japanese Musculoskeletal Oncology Group (JMOG)

Abstract: We analyzed the outcome of 80 patients with periacetabular tumors undergoing C-THA reconstruction. The rates of postoperative complication were still high, but comparable to those in previous studies. Our results suggest wound management using a RAM flap is useful for reducing wound complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 41 publications
0
23
1
Order By: Relevance
“…However, pseudoatrosis during such operations was unstable and painful, and ischiofemoral or ileofemoral arthrodesis the treatment results were unsatisfactory, and also led to a significant discrepancy in the length of the limbs and difficulties with sitting and walking. According to studies on the use of allografts, good treatment results were achieved, however, complications in the form of allograft fractures and infectious complications were observed in this category of patients (Brown et al, 2018;Ogura et al, 2018). To date, the use of saddles Mark II is widely used in reconstructions after resection of the pelvic bones of type II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pseudoatrosis during such operations was unstable and painful, and ischiofemoral or ileofemoral arthrodesis the treatment results were unsatisfactory, and also led to a significant discrepancy in the length of the limbs and difficulties with sitting and walking. According to studies on the use of allografts, good treatment results were achieved, however, complications in the form of allograft fractures and infectious complications were observed in this category of patients (Brown et al, 2018;Ogura et al, 2018). To date, the use of saddles Mark II is widely used in reconstructions after resection of the pelvic bones of type II.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the use of saddles Mark II is widely used in reconstructions after resection of the pelvic bones of type II. A number of studies have shown good treatment results, while the number of various complications remains high (53%) (Ogura et al, 2018;Widana et al, 2021). Although reconstruction using allografts is one of the most common reconstruction options, a study of the results of existing studies shows that it is associated with a high frequency of complications, including fractures, the absence of bone fusion and infection (Brown et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…EARs of the joint are technically challenging and prone to significant complications and morbidity (4,(6)(7)(8)15). Although the technique is well known for the knee joint, fewer information exists with regard to its use in the hip joint (4,5,9).…”
Section: Discussionmentioning
confidence: 99%
“…When performed in an expert centre, EAR of the joint is associated with adequate margins and little local recurrence. EAR and wide resection of the hip joint have been reported in few series (4,5,9). without a significant difference in outcomes between resections of PMBTs located in the pelvis and proximal femur.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation